INTERVENTION TO INCREASE BREAST MILK PRODUCTION:LITERATURE REVIEW - Sukmawati Sukmawati; Aditya Nugraha; Agnes Dwi; Amiatun Amiatun; An Nisa Apriliani; Anggi Ramdani; Asep Nugraha; Tasya Puja Yarsita (Journal of Maternity Care and Reproductive Health, 2020)
Exclusive breastfeeding coverage in Indonesia is still below the National target. Breast milk is the best nutrition for babies and affects the growth and development of babies. One of the reasons for the low coverage of exclusive breastfeeding is the lack of milk production, so that various interventions are needed to increase milk production. This literature study aims to determine interventions to increase breast milk production. The research method uses Narrative Literature Review. The database used by Google Scholar, Pubmed, and Sciencedirect with the keywords Breast Milk "OR" Lactation "OR" Milk Secretion "AND" Nursing Intervention. The inclusion criteria used were English-language articles, publication year 2015-2020, accredited in Sinta and Scoppus, full text available with a focus on seeking interventions to increase breast milk production. The search results obtained 1435 articles after screening according to keywords and search focus, 7 articles were analyzed. The results of the literature review were obtained: interventions to increase breast milk production with non-pharmacological techniques, namely acupuncture, consumption of herbal and ginger teas, breast care or breast massage, skin-to-skin contact between mothers and babies and domperidone pharmacological techniques. The article that has been analyzed shows its effectiveness in increasing milk production because it stimulates prolactin which helps increase milk production. Conclusion: interventions to increase breast milk production using non-pharmacological and pharmacological techniques can increase milk production. The results of this literature review are expected to become a reference in an effort to increase breast milk production.